Faktor-Faktor yang Berhubungan dengan Pemberian Asi Eksklusif di Desa Sukamerta Kecamatan Rawamerta - Yuliyanti Sari; Lili Farlikhatun (Jurnal Keperawatan Muhammadiyah, 2023)
Background: The mortality of 88% of infants due to infection can be reduced by breastfeeding, but the lack of understanding of the importance of breastfeeding for infants has resulted in the exclusive breastfeeding program not taking place optimally. Mother's understanding in breastfeeding cannot be separated from various factors that influence it.Objective: This study aims to determine the factors related to exclusive breastfeeding in Sukamerta Village, Rawamerta District in 2022.Methods: This research method used an observational analytic research design with a cross sectional design with independent variables including age, education, occupation, parity, and gestational distance, while the dependent variable is exclusive breastfeeding. The population in this study were mothers who had babies aged 6-12 totaling 52 people using a purposive sampling technique and a total sample that made the entire population as a sample. Data analysis was performed using univariate analysis to explain the characteristics of the study and bivariate analysis using SPSS chy-square test.Result: The results of this study found that the relationship between age and exclusive breastfeeding was seen as the Asymp.sign value of 0.120, because the p-value was 0.120 > 0.05. The relationship between education and exclusive breastfeeding shows the Asymp.sign value of 0.456, because the p-value is 0.456 > 0.05. The relationship between employment and exclusive breastfeeding is seen as the Asymp.sign value of 0.000, because the p-value is 0.000 <0.05. The relationship between parity and exclusive breastfeeding was seen as the Asymp.sign value of 0.011 because the p-value was 0.011 < 0.05. The relationship between pregnancy distance and exclusive breastfeeding was seen as the Asymp.sign value of 0.001 because the p-value was 0.001 < 0.05.Conclusions: The conclusion of this study is that there is no relationship between age and education with exclusive breastfeeding, but there is a relationship between work, parity, and distance between pregnancies and exclusive breastfeeding